(untitled) (Research, Society and Development, 2020)
This paper discusses teacher training in Brazil, which is formed by a multicultural and multi-ethnic society, however, in the initial training courses and in the official curriculum of the school, the Eurocentric, Christian, heterosexual and white ideology is still produced. It aims to discuss the need for inclusion in the central axis of the curricular organization of teacher training courses, more subjects that discuss the theme related to traditional Brazilian communities. Qualitative research was carried out, combined with content analysis. The results showed that the discussion of the topic in the classroom occurs only on specific dates. It is concluded that the current initial teacher training needs to be rethought and curricular realignment.